Isolation and characterization of equine amniotic membrane-derived mesenchymal stem cells - Seo, M.S., Seoul National University, Seoul, Republic of Korea; Park, S.B., Seoul National University, Seoul, Republic of Korea; Kim, H.S., Seoul National University, Seoul, Republic of Korea; Kang, J.G., Seoul National University, Seoul, Republic of Korea; Chae, J.S., Seoul National University, Seoul, Republic of Korea; Kang, K.S., Seoul National University, Seoul, Republic of Korea (Journal of veterinary science (Suwŏn-si, Korea), 2013)
Recent studies have shown that mesenchymal stem cells are able to differentiate into multi-lineage cells such as adipocytes, chondroblasts, and osteoblasts. Amniotic membrane from whole placenta is a good source of stem cells in humals. This membrane can potentially be used for wound healing and corneal surface reconstruction. More, it can be easily obtained after delivery and is usually discarded as classified waste.